The separation of alkyldiethanolamide based on Kernel oil of Calophyllum inophillum fruit using High-Performance Liquid Chromatography - Iqbal, Masrori; Suhendra, Dedy; Ryantin Gunawan, Erin (Acta Chimica Asiana, 2022)
This study aimed to separate the synthesized alkyldiethanolamide from kernel oil Calophyllum inophyllum (Local name: Nyamplung) using High-Performance Liquid Chromatography (HPLC). HPLC column utilized was SGE ODS-2 reverse phase and UV detector 213 nm. The variables to obtain the optimum conditions for separating alkyldiethanolamide were mobile phase and flow rate. The mobile phase composition and the optimum separation flow rate obtained acetonitrile: water (90:10) and 1.5 mL/minute, respectively. The percentage compositions of amide fatty acids that had been successfully synthesized based on HPLC were linoleoyl diethanolamide (46-49%), oleoyl diethanolamide (27-29%), palmitoyl diethanolamide (11-14%), and stearoyl diethanolamide (9-11%).